2006
DOI: 10.1523/jneurosci.1726-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cell Line-Derived Neurotrophic Factor Family Members Sensitize NociceptorsIn Vitroand Produce Thermal HyperalgesiaIn Vivo

Abstract: Nerve growth factor (NGF) has been implicated as an effector of inflammatory pain because it sensitizes primary afferents to noxious thermal, mechanical, and chemical [e.g., capsaicin, a transient receptor potential vanilloid receptor 1 (TRPV1) agonist] stimuli and because NGF levels increase during inflammation. Here, we report the ability of glial cell line-derived neurotrophic factor (GDNF) family members artemin, neurturin and GDNF to potentiate TRPV1 signaling and to induce behavioral hyperalgesia. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
255
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(276 citation statements)
references
References 67 publications
17
255
1
3
Order By: Relevance
“…The molecular processes whereby NGF/TrkA activation leads to heat hyperalgesia are well-documented (7), but to date, the molecular nature of GFL signaling on nociception has yet to be elucidated. For example, we and others have shown that acute exposure of GFLs, including artemin, in vivo leads to heat hyperalgesia (8,42,45). Similarly, GFLs potentiate capsaicin responses in dissociated DRG neurons recorded by Ca 2+ imaging, showing sensitization of TRPV1 + cells (45).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The molecular processes whereby NGF/TrkA activation leads to heat hyperalgesia are well-documented (7), but to date, the molecular nature of GFL signaling on nociception has yet to be elucidated. For example, we and others have shown that acute exposure of GFLs, including artemin, in vivo leads to heat hyperalgesia (8,42,45). Similarly, GFLs potentiate capsaicin responses in dissociated DRG neurons recorded by Ca 2+ imaging, showing sensitization of TRPV1 + cells (45).…”
Section: Discussionmentioning
confidence: 75%
“…For example, we and others have shown that acute exposure of GFLs, including artemin, in vivo leads to heat hyperalgesia (8,42,45). Similarly, GFLs potentiate capsaicin responses in dissociated DRG neurons recorded by Ca 2+ imaging, showing sensitization of TRPV1 + cells (45). However, specific changes in TRPV1 channel activity have not been reported, and the preponderance of data suggests that artemin-induced heat hyperalgesia is caused by increased TRPV1 expression (27,28,46,47).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Chez l'adulte, ces facteurs neurotrophiques régulent également les propriétés fonctionnelles des nocicepteurs et leur expression est augmentée lors de l'inflammation tissulaire. L'injection de NGF, comme celle de GDNF, d'artémine ou de neurturine, induit une hyperalgé-sie thermique et mécanique, mimant une hyperalgésie inflammatoire [4]. Une des cibles moléculaires de l'effet pro-algique du NGF et de l'artémine est le récepteur TRPV1 (transient receptor potential vanilloid 1) [4][5][6].…”
unclassified
“…L'injection de NGF, comme celle de GDNF, d'artémine ou de neurturine, induit une hyperalgé-sie thermique et mécanique, mimant une hyperalgésie inflammatoire [4]. Une des cibles moléculaires de l'effet pro-algique du NGF et de l'artémine est le récepteur TRPV1 (transient receptor potential vanilloid 1) [4][5][6]. En effet, il n'existe pas d'hyperalgésie secondaire à l'inflammation ni d'hyperalgésie thermique induites par le NGF chez les souris dont le gène TRPV1 a été invalidé [7][8][9].…”
unclassified